Thermo-sensitive chitosan-cellulose derivative hydrogels: swelling behaviour and morphologic studies - Barros, Sandra Cerqueira; Silva, Ana Alves da; Costa, Diana Barbosa; Cesarino, Ivana [UNESP]; Costa, Carlos M.; Lanceros-Mendez, Senentxu; Pawlicka, Agnieszka; Silva, Maria Manuela (Springer, 2014)
Hydrogels are three-dimensional, hydrophilic, polymer networks that are able to imbibe large amounts of water or biological fluids, while maintaining their dimensional stability. The polymer binding might be achieved by chemical or physical interactions. Physical crosslinking of a polymer to form its hydrogel, might be accomplished either by casting-solvent evaporation (SC) method or by freeze-thaw (FT) technique. The physical hydrogels, especially the ones based on natural biopolymers, like polysaccharides, are being widely used in industry and medicine due to their favourable properties: biocompatibility; biodegradability; low toxicity and eco-friendly characteristics. Polysaccharides, like chitosan (CH) and (hydroxypropyl)methyl cellulose (HPMC) have gained great attention due to its stimuli sensitive properties: pH and temperature responsiveness, respectively. Thus, within this work we have developed physically crosslinked CH:HPMC hydrogel films, using both SC and FT techniques. The attained CH:HPMC membranes were evaluated in terms of their swelling, thermal (low critical solution temperature-LCST), structural (attenuated total reflectance Fourier transform infrared spectroscopy) and morphological (scanning electron microscopy and atomic force microscopy) properties. According to these results, the developed membranes exhibit a good miscibility between the two component biopolymers. Moreover, the CH:HPMC membranes exhibit a high swelling capacity (SWFT = 1,172 and SWSC = 7,323), a low surface roughness (Sq = 5.6-9.5 nm) and an elevated LCST (LCST = 85.2-87.5 A degrees C). The stimuli sensitive behaviour makes hydrogels appealing for the design of smart devices applicable in a variety of technological fields. In our particular case, we envisage the application of such materials as active substances (moisturisers, antiperspirants and scents) delivers, into textile substrates in a controlled manner.
Keywords: Chitosan; (Hydroxypropyl)methyl cellulose; Swelling; LCST